Nursing diagnosis in the immediate postoperative of valve replacement surgery - Lara, Bruna Fontes de (2017)
Aim: To identify the nursing diagnoses in the immediate postoperative period of valve replacement surgery. Method: Documental and cross-sectional study carried out by means of the medical records of patients submitted to valve surgeries between January and December 2014, in a large hospital specialized in cardiology in the state of São Paulo. Results: among the 50 analyzed charts, 58% belonged to female patients. Eleven nursing diagnoses were identified, 55% are classified by the health problem and 45% are risk. The most prevalent nursing diagnoses were Infection Risk (100%), Impaired Physical Mobility (94%) and Risk of Fall (94%). Conclusion: the highest occurrence diagnosis identified in the immediate postoperative period of surgery was the risk of infection. The identified diagnoses allowed a better understanding of the experience lived by the patient and the nurses' perception of it, contributing to the optimization of human and material resources.